A real-world study of clofarabine and cytarabine combination therapy for patients with acute myeloid leukemia. Issue 10 (3rd October 2018) - He, Fiona; Sapkota, Smarika; Parker, Sarah; Defor, Todd; Warlick, Erica; Ustun, Celalettin; Eckfeldt, Craig; Rashidi, Armin; Kurtzweil, Andy; Weisdorf, Daniel; Bejanyan, Nelli
Abstract: Clofarabine and cytarabine (Clo + Ara-C) combinations have efficacy in treatment of acute myeloid leukemia (AML). We retrospectively analyzed clinical outcomes of 71 AML patients receiving Clo + Ara-C regimens at the University of Minnesota from 2011 to 2016: 44 patients (62%) had newly diagnosed AML and 27 patients (38%) had relapsed/refractory AML. The median age of patients was 69 years (interquartile range [IQR], 63–75 years). Nearly 60% of the patients had secondary AML, and about half of patients had adverse risk cytogenetics. Objective response rate (ORR) was 42% in all patients with complete remission (CR) rate of 20%. Progression-free survival (PFS) at 2 years was 16% (95% CI 8–27%) and overall survival (OS) at 2 years was 21% (95% CI 11–33%) for all patients. The 30-day mortality rate was 18%. Clo + Ara-C- containing regimens are an acceptable upfront therapy option for patients who are not candidates for "7 + 3" induction, but do not induce durable remissions.